Peningkatan Pertumbuhan Ekonomi di Jawa Timur Pengaruh BI 7 Days Repo Rate, Tingkat Inflasi, dan Jumlah Uang Beredar - Achmad Rizal Fardiansah; Lativa Hartiningtyas (Ekonomis: Journal of Economics and Business, 2023)
In recent years, applied researcher have become increasing interested in economic growth. However, economic growth is difficult to detect because of the many influencing factors. The present study was conducted to evaluate possibility there is influence from the BI 7 days repo rate, the inflation rate, and the money supply on the level of economic growth in east java. This study uses multiple linear regression, the results show simultaneously and partially of the BI 7 days repo rate, inflation, and the money supply, have a significant effect on economic growth in East Java.